Peran Teknologi dalam Tranformasi Tradisi Siri’ Na Pacce Terhadap Generasi Z di Kota Makassar - Alifka Alya Zhafirah; Nur Rezky Asman; Muhammad Rasyid Ridha (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study examines the role of technology in the transformation of Siri' na Pacce cultural values among the Z generation in Makassar City. The values of Siri' (shame) and Pacce (pain) are deeply rooted philosophical foundations in Bugis-Makassar society, but face relevance challenges in the digital era. Through a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation, this study analyzes how digital media such as Instagram, YouTube, and TikTok act as a means of transmitting traditional cultural values. The results show that technology facilitates the dissemination of Siri' na Pacce values in a broader and more engaging way for generation Z, while transforming cultural understanding from what was previously perceived as a culture of violence to civilized values. This research concludes that there is a need for synergy between digital technology, family and educational institutions to ensure that Generation Z does not only know the value of Siri' na Pacce superficially, but is able to internalize and implement it in daily life according to the context of the times.